2015
DOI: 10.46784/e-avm.v7i1.120
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Canine Monocytic Ehrlichiosis in Hunting Dogs in the Autonomous Province of Vojvodina, Serbia

Abstract: Canine monocytic ehrlichiosis is a bacterial, vector-transmitted infection caused by Ehrlichia canis. Th e pathogen is mainly transmitted by ticks Rhipicephalus sanguineus. The disease highest distributionis most widely distributed in tropical and subtropical countries but it is also reported in Mediterranean countries of Europe (Spain, France, Italy, Turkey). Temperate continental climate and presence of these tick species are responsible for the maintenance and spreading of canine monocytic ehrlichiosis with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Previous research has confirmed that R. sanguineus most often infests dogs in our country as well (Bogunović et al., 2018 ; Potkonjak et al., 2016 ). Even though previous seroepidemiological studies conducted in Serbia have confirmed the exposure of dogs to E. canis (Bogićević et al., 2017 ; Potkonjak et al., 2013 ), clinical cases of CME or molecular confirmation of the causative agent have not been reported before (Kovačević Filipović et al., 2018 ). Also, the presence of E. canis in R. sanguineus ticks collected from dogs in Serbia has not been confirmed so far (Potkonjak et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has confirmed that R. sanguineus most often infests dogs in our country as well (Bogunović et al., 2018 ; Potkonjak et al., 2016 ). Even though previous seroepidemiological studies conducted in Serbia have confirmed the exposure of dogs to E. canis (Bogićević et al., 2017 ; Potkonjak et al., 2013 ), clinical cases of CME or molecular confirmation of the causative agent have not been reported before (Kovačević Filipović et al., 2018 ). Also, the presence of E. canis in R. sanguineus ticks collected from dogs in Serbia has not been confirmed so far (Potkonjak et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, A. phagocytophilum infection was confirmed in the family’'s dogs. Domestic dogs are considered as potential reservoirs for this pathogen in Serbia [ 34 ]. A. phagocytophilum is the causative agent of granulocytic anaplasmosis in humans and animals.…”
Section: Discussionmentioning
confidence: 99%
“…Serological studies conducted in dogs in Serbia confirmed they are exposed to A. phagocytophilum. Using the immunofluorescence antibody test (IFAT), a seroprevalence of 15.5% was recorded in analyzed dogs from Vojvodina (Potkonjak et al, 2015), while dogs from Belgrade had a seroprevalence of 26.1% (Kovačević Filipović et al, 2018). Although previous studies indicate that dogs are exposed to the causative agent of canine anaplasmosis, there have been no confirmed cases of this disease in Serbia to date.…”
Section: Role Of Jackals and Foxes In The Epidemiology Of Tick-borne mentioning
confidence: 98%